Antibacterial and biosurfactant activity of endophytic bacteria isolated from mangrove plant in Lamongan, Indonesia - FATIMAH FATIMAH; NAZIL DWI RAHAYUNINGTYAS; ALIFAH NASTITI; DELA DWI ALAWIYAH; RICO RAMADHAN; ALMANDO GERALDI; JUNAIRIAH JUNAIRIAH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Fatimah, Rahayuningtyas ND, Nastiti A, Alawiyah DD, Ramadhan E, Geraldi A, Junairiah. 2024. Antibacterial and biosurfactant activity of endophytic bacteria isolated from mangrove plant in Lamongan, Indonesia. Biodiversitas 25: 3035-3042. This study aims to determine the antibacterial and biosurfactant activity of 61 endophytic bacteria from mangrove plants in Kutang Lamongan Beach. Antibacterial screening of supernatant of endophytic bacteria was performed using the disc diffusion method against Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923. The most potent isolate was identified using 16s rRNA. The chemical compounds of the most potent isolate were identified using GC-MS analysis. The data were analyzed descriptively. Biosurfactant activity was also performed on the most potential isolate. All the isolates showed inhibitory zones against E. coli and S. aureus. Isolate LMG-2 produced the highest antimicrobial activity, averaging 9.57±0.4 mm against E. coli and 8.87±0.36 mm against S. aureus. The biosurfactant activity of LMG-2 isolate produced a surface tension of 39.09+0.49 mN/m and emulsification activity of 65.03+0.03% against kerosene, 47.63+0.10% against crude oil and 46.53+0.27 to diesel. The isolate LMG-2 had 98,41% similarity with the Bacillus amyloliquefaciens strain NBRC 15535 with a query cover of 100%. The biosurfactant extract contains 9-octadecenoic acid methyl ester, (E)-, 9,12-octadecadienoic acid (Z, Z) methyl ester, and 9,12,15-octadecadienoic acid methyl ester. These compounds, known as Fatty Acid Methyl Esters (FAMEs), were integral components of biosurfactants, surface-active agents produced by microorganisms.